Dynamics Performance Analysis of Metro Vehicle-Turnout System Based on Rigid-Flexible Coupled Model - LI Huawei; XU Xiaotang; LIU Wei; HE Jun (Chengshi guidao jiaotong yanjiu)
[Objective] To investigate the safety of metro vehicles passing through No.12 turnouts in both lateral and forward directions, providing a theoretical basis for the optimization and maintenance of turnout structures, it is necessary to study the dynamic performance of a metro vehicle-turnout coupling model. [Method] Based on the theory of rigid-flexible coupled dynamics, a coupled dynamic model comprising three subsystems—vehicle, wheel-rail, and turnout—is established. By simulating the operating conditions of vehicles passing through the turnout laterally and forward, key indicators such as wheel-rail vertical and lateral forces, wheelset lateral force, derailment coefficient, and dynamic wheel load reduction ratio are analyzed. [Result & Conclusion] Under both lateral and forward passing conditions, the maximum wheel-rail vertical force will not exceed the allowable threshold, and both wheel-rail lateral force and wheelset lateral force remain within the dynamic equilibrium range. The derailment coefficient remains below the critical limit, and the dynamic wheel load reduction ratio is consistently lower than the safety threshold. This research confirms that the metro vehicle-turnout coupling model based on rigid-flexible coupled dynamics can effectively evaluate the safety of vehicle passage through turnout.